REASONS FOR LEAVING THE LAST PLACE OF RESIDENCE BY RETURN MIGRANTS DURING COVID-19: A SOCIOLOGICAL ANALYSIS (International Journal of Food and Nutritional Sciences, 2022)
Introduction: Medical Sociology is "the study of health care as it is institutionalized in a society and of health,or illness and its relationship to social factors". Migration is the term used to describe the temporary orpermanent relocation of a person's usual place of living across space during a given period. This study focuseson international return migration, defined as returning to one's country of citizenship after being aninternational migrant abroad for at least a year.Aims: to evaluate the respondents' socioeconomic status and the reasons for leaving the last place of residenceby respondents.Methods: 100 participants were surveyed using planned interviews and observation as part of the currentstudy's information collection process. Through purposeful sampling, the respondents were selected.Results: The results showed that most respondents (43%) are between the ages of 51 and 60 years; 64% ofrespondents are men; 56% of respondents identify as Hindu; 39% of respondents are undergraduates; and 82 %of the respondents are married and according to second objective the findings are as follows, the majority(61%) of the respondents returned from urban to rural, 65% of the respondents return by naturaldisaster/pandemic, 55% of the respondents reason for return is unemployment/employment Situation, 39%ofthe respondents reason to return is life security, 55% of the respondents reason for return is worse governancepolicy, 62% of the respondent's reason for return is a health condition and 45% of the respondents cause ofreturn was voluntary with assistance.